Climate Change and Public Health in Bangladesh: Perceptions, Vulnerabilities, and Empirical Evidence from Coastal Communities - Ali, Kazi Md Barkat; Ferdos, Jannatul; Molla, Morshed Hossan (Journal of Sustainability and Environmental Management, 2025)
Coastal communities in Bangladesh are increasingly vulnerable to the impacts of climate change. These effects worsen health issues and hinder access to essential healthcare services. This study explores the challenges these communities face in climate change awareness, health outcomes, and healthcare access. It focuses on gender disparities, climate-induced disasters, and healthcare infrastructure. The study used a mixed-methods approach, combining quantitative surveys and qualitative interviews with coastal residents from Banshkhali and Kutubdia sub-districts. It assessed their perceptions of climate change, its health impacts, and healthcare access. Statistical analyses, including Chi-square tests and p-values, revealed significant relationships between climate-induced disasters, such as floods, cyclones, and sea-level rise, and health problems. These include respiratory disorders, mosquito-borne diseases, and mental health issues. The study also highlighted gender disparities in climate change awareness. Men were more informed due to their outdoor occupations. Women faced barriers to information access because of restricted mobility and limited communication channels. The study identified critical gaps in disaster management services and awareness of the Bangladesh Health Policy 2011. These gaps further intensified vulnerabilities. Despite modern healthcare options, 14% of residents still relied on indigenous treatments. This highlights the need for an integrated healthcare approach. The study concludes with recommendations for gender-sensitive climate communication, integrating indigenous knowledge with modern healthcare, strengthening disaster preparedness, and raising awareness of health policies. These strategies are crucial for enhancing climate resilience and ensuring equitable healthcare for coastal communities facing the dual challenges of climate change and health disparities.